Chinese historical microdemography - Harrell, Stevan (Studies on China, 1995)
Using local studies to answer global questions, this compilation challenges traditional notions concerning historical Chinese population trends. Genealogies, epitaphs, and household registers are some of the local and primary materials used to examine the important issues of fertility, mortality, family structure, and migration patterns.